Maximal open compact subgroup of the projective symplectic group over a locally compact discrete valuation field (1971)
For the purpose of describing maximal arithmetic groups one tecnique would be to study the local correspondent problem and then try to put the local results together. The general theory of Hijikata and Beuhat-Tits handles the local case. However in order to globalize one needs to know precise information about the orders and latt ice involved. This is an expository note with the objective of providing the information we need to give complete proofs to the results announced [5].